Polymer Composites with Metal Nanoparticles: Synthesis, Properties, and Applications. Synthesis, Properties, and Applications. - Zapata-Ramirez, P (Elsevier, 2018)
Gold (AuNPs) and silver (AgNPs) nanoparticles have unique physical and chemical properties opening the focus on polymer/metal nanocomposites to develop materials with new characteristics. Polymers with AuNPs or AgNPs are recognized as one of the best routes to obtain novel materials having a broad range of properties, such as high long term antimicrobial activity, catalytic activity in diverse types of reactions, and conductivity properties. Therefore, these nanocomposites have a wide field of application.In the current chapter, synthesis routes for obtaining silver and gold nanoparticles and their functionalization to improve nanoparticle dispersion in the matrix are described. The main routes for nanocomposite preparation and their influence on the polymer composite properties are also explained. This chapter describes the characteristics and applications of polymer/AuNPs or AgNPs nanocomposites for water treatment, in the textile industry, food packaging, sensors, and medical devices. © 2019 Elsevier Inc. All rights reserved..